Antibacterial repair-promoting composite nano-enzyme and preparation method thereof
By developing a composite nanobine enzyme that promotes antibacterial repair and uses the synergistic role of various ingredients to solve the problem of complex antibiotic resistance and growth factors in traditional wound treatment methods, and achieve efficient sterilization and promoting wound healing.
Patent Information
- Application Number
- CN202411886143.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When existing wound treatment methods face antibiotic resistance problems, it is difficult to achieve efficient and rapid healing. The traditional growth factor extraction and purification process is complex and costly, which may cause allergic reactions or other adverse reactions.
Develop a composite nanobase that is antibacterially promoted, and components such as combining carboxymethyling base shell, FE-CDS monocular nanozymes, modified CEO2 nanoparticles, lysine, silk protein, and pentahydrolytic ingredients to form a possession Antibacterial and repair dual -function composite hydrogel materials.
It achieves efficient sterilization and promotion of tissue repair in the wound environment. Through the synergistic effect of multiple components, it significantly improves wound healing efficiency, reduces oxidative damage to healthy tissue, and controls the release of active ingredients.
Smart Images

Figure CN119326724A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial nanomaterials, and specifically relates to an antibacterial and repair-promoting composite nanozyme and a preparation method thereof. Background Art
[0002] Wound trauma is a common clinical problem, including acute trauma (such as cuts and burns) and chronic wounds (such as diabetic foot ulcers and pressure sores). These wounds not only significantly affect the patient's quality of life, but may also cause serious complications such as infection, gangrene and even sepsis. Therefore, wound management has become a major challenge in clinical medicine. At present, commonly used wound treatment methods in clinical practice include debridement, bandaging, the use of antibiotics and growth factors. However, the efficacy of these methods is limited, especially when faced with the problem of antibiotic resistance, traditional treatment methods often cannot meet the needs of efficient and rapid healing. Long-term use of antibiotics can easily lead to an increase in bacterial resistance, making infections more difficult to control; the extraction and purification process of natural growth factors is complicated and costly, which limits their widespread application; some topical medications may cause allergic reactions or other adverse reactions.
[0003] Nanozymes are nanomaterials with catalytic activity similar to that of natural enzymes. Compared with traditional antibacterial materials, nanozymes show unique advantages. Nanozymes can effectively kill or inhibit bacterial growth through a variety of mechanisms; for example, peroxidase-like nanozymes can catalyze hydrogen peroxide (H2O2) to generate highly toxic hydroxyl radicals (-OH), which can destroy bacterial cell membranes and inhibit bacterial metabolism. At the same time, the high specific surface area and strong adsorption capacity of nanozymes make it easier to attach to the wound surface, enhance the antibacterial effect and achieve sustained release of antibacterial ingredients; some nanozymes (such as CeO2 and MnO2-based materials) have superoxide dismutase (SOD) and catalase (CAT)-like activities, which can remove excess reactive oxygen species (ROS) in the wound microenvironment and reduce oxidative stress damage to tissue cells. In addition, nanozymes can simulate the effects of natural growth factors, activate cell signaling pathways, promote cell proliferation, differentiation and migration, and accelerate wound healing. In terms of adaptability to complex wounds, the catalytic performance of nanozymes is significantly enhanced in wound environments with low pH, high ROS or rich in H2O2, which is more conducive to the treatment of infected wounds (such as diabetic foot ulcers) and chronic wounds. In the process of wound healing, antibacterial and tissue repair are two key steps, but there is often a contradiction between the two. For example, although potent antibacterial agents can quickly inhibit infection, they may cause certain toxicity to host tissues, and materials that simply promote repair are difficult to solve the infection problem. Therefore, based on the above problems, it is extremely necessary to develop a composite nanozyme material that effectively inhibits bacteria and promotes tissue repair. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide an antibacterial and repair-promoting composite nanozyme and a preparation method thereof.
[0005] The technical effect described in the present invention is achieved through the following technical scheme: an antibacterial and repair-promoting composite nanozyme, which is composed of a main matrix and a core matrix. The main matrix is composed of the following raw materials: carboxymethyl chitosan, Fe-CDs single-atom nanozyme, modified CeO2 nanoparticles, lysine, silk fibroin, and glutaraldehyde; the core matrix is composed of the following raw materials: PLGA, dichloromethane, glutathione, vitamin E, sodium hyaluronate, glycine, and Tween-80.
[0006] Preferably, the specific preparation steps of the carboxymethyl chitosan are as follows: A1: Add chitosan to isopropanol, stir and mix evenly to obtain a chitosan suspension with a concentration of 3-5wt%; add sodium hydroxide to deionized water, stir and mix evenly, then slowly add it to the chitosan suspension, stir at 300rpm for 30-50min, to obtain pretreated chitosan; A2: Add chloroacetic acid to deionized water, stir to dissolve evenly, then slowly add to the pretreated chitosan prepared in step A1, heat in a water bath to 50-60°C, react for 3-4 hours, adjust the pH to neutral, filter, wash with deionized water and ethanol repeatedly for 3 times, and vacuum dry at 50°C to constant weight to obtain carboxymethyl chitosan; Preferably, in step A1, the ratio of the amount of sodium hydroxide, deionized water and chitosan suspension is 1 g: 4-5 mL: 15-20 mL; Preferably, in step A2, the ratio of the amount of chloroacetic acid, deionized water and pretreated chitosan is 0.05-0.1 g: 0.5 mL: 1 mL.
[0007] Preferably, the specific preparation steps of the Fe-CDs single-atom nanozyme are as follows: B1: Dissolve glucose in deionized water and stir thoroughly until completely dissolved to obtain a carbon source solution with a concentration of 10-12wt%; dissolve ferric chloride in deionized water and stir thoroughly until completely dissolved to obtain an iron source solution with a concentration of 5-6wt%; slowly add the iron source solution to the carbon source solution, add polyethylene glycol, stir and dissolve evenly to obtain a precursor solution; B2: Add the precursor solution prepared in step B1 into a polytetrafluoroethylene reactor, set the hydrothermal reaction temperature to 180-200°C, react for 6-12 hours, and after the reaction is completed, naturally cool to room temperature, wash with deionized water and anhydrous ethanol repeatedly for 3 times, and vacuum dry at 60°C to constant weight to obtain Fe-CDs precursor powder; B3: The Fe-CDs precursor powder prepared in step B2 is calcined at high temperature, protected by nitrogen atmosphere, and the heating rate is set to 5°C / min, and the temperature is raised to 450-600°C. After maintaining the temperature for 2-4 hours, it is naturally cooled to room temperature to obtain Fe-CDs single-atom nanozymes; Preferably, in step B1, the volume ratio of the iron source solution to the carbon source solution is 4-5:1; and the amount of polyethylene glycol added is 10% of the total mass of glucose and ferric chloride.
[0008] Preferably, the specific preparation steps of the modified CeO2 nanoparticles are as follows: C1: dissolve cerium chloride in deionized water, stir and dissolve evenly to obtain a cerium chloride precursor solution with a concentration of 2-3wt%; gradually add 2 M ammonia water to the cerium chloride precursor solution, adjust the pH to 9-10, stir continuously at 300 pm for 30-50 min, centrifuge at 8000 rpm for 10 min, filter, wash with deionized water and ethanol repeatedly for 3 times, vacuum dry at 60°C for 6-12 h, and then calcine at 400-500°C for 2 h in an air atmosphere to obtain CeO2 nanoparticles; C2: dissolving polyethylene glycol in deionized water, stirring and dissolving uniformly, obtaining a polyethylene glycol solution with a concentration of 5 to 10 wt%; adding the CeO2 nanoparticles prepared in step C1 to deionized water, ultrasonically treating at 60 to 80 W and 40 kHz for 10 to 15 min, obtaining a CeO2 dispersion with a concentration of 0.5 to 1 wt%; C3: slowly drop the CeO2 dispersion prepared in step C2 into the polyethylene glycol solution prepared in step C2, stir at 300 rpm at 50-70°C for 4 h, centrifuge at 10000 rpm for 10 min, filter, wash with deionized water and anhydrous ethanol for 3 times, and vacuum dry at 60°C to constant weight to obtain modified CeO2 nanoparticles; Preferably, in step C3, the volume ratio of the CeO2 dispersion to the polyethylene glycol solution is 1 to 1.5:1.
[0009] Preferably, another aspect of the present invention is to provide a method for preparing an antibacterial and repair-promoting composite nanozyme, and the specific preparation steps are as follows: S1: dissolving glutathione, sodium hyaluronate and glycine in deionized water, stirring and dissolving them uniformly to obtain an inner aqueous phase; dissolving PLGA in dichloromethane, stirring and dissolving them uniformly to obtain an organic phase; S2: slowly add the inner aqueous phase prepared in step S1 to the organic phase prepared in step S1, perform ultrasonic treatment at 300W for 20 to 40 seconds in an ice bath, then add vitamin E, continue ultrasonic treatment for 5 seconds to obtain a primary emulsion; add Tween-80 to deionized water, stir and mix evenly to obtain an external aqueous phase with a concentration of 0.5wt%; S3: slowly adding the primary emulsion prepared in step S2 to the external aqueous phase prepared in step S2, ultrasonically treating at 300W for 30-60s in an ice bath, then stirring at 300rpm for 4h at room temperature, centrifuging at 8000rpm for 10min, filtering, washing with deionized water, and vacuum drying at 60°C for 8-12h to obtain PLGA microcapsules; S4: dissolving carboxymethyl chitosan in deionized water, adjusting the pH to 6.5, stirring and dissolving uniformly, and obtaining a carboxymethyl chitosan solution with a concentration of 1wt%; dispersing the modified CeO2 nanoparticles in deionized water, dispersing them uniformly by ultrasonic treatment, and then slowly adding them to the carboxymethyl chitosan solution, stirring and mixing uniformly, and then adding Fe-CDs single-atom nanozymes, stirring and mixing uniformly, and obtaining a mixed solution; S5: Lysine, silk fibroin and PLGA microcapsules prepared in step S3 are sequentially added to the mixed solution prepared in step S4, stirred and mixed evenly, ultrasonically treated at 40-60W for 3-5min, slowly added with a 2.5wt% glutaraldehyde solution prepared with deionized water, adjusted to pH 7.4, stirred and reacted for 30-60min at room temperature, allowed to stand at 4°C for 12-24h, washed with deionized water, and dried naturally to obtain a composite nanozyme.
[0010] Preferably, in step S1, the ratio of the amount of glutathione, sodium hyaluronate, glycine and deionized water is 0.4-0.6 g: 0.5-0.6 g: 0.1-0.2 g: 100 mL; the ratio of the amount of PLGA and dichloromethane is 1 g: 60-100 mL; Preferably, in step S2, the volume ratio of the inner aqueous phase to the organic phase is 1:3-5; the added concentration of vitamin E is 1.5-2 mg / mL; Preferably, in step S3, the volume ratio of the primary emulsion to the external aqueous phase is 1:4-5; Preferably, in step S4, the ratio of the amount of the modified CeO2 nanoparticles, deionized water and carboxymethyl chitosan solution is 0.5-1 g: 20 mL: 100 mL; the ratio of the amount of the Fe-CDs single-atom nanozyme and carboxymethyl chitosan solution is 0.1-0.5 g: 100 mL; Preferably, in step S5, the ratio of the amount of lysine, silk fibroin, PLGA microcapsules and the mixed solution is 0.5-0.6 g: 0.5-1 g: 2-5 g: 100 mL; the amount of glutaraldehyde solution added is 2-5% of the volume of the mixed solution.
[0011] The beneficial effects of the present invention are as follows: The present invention prepares a composite hydrogel material with dual functions of antibacterial and repair promotion through the synergistic effect of multiple components. First, polyethylene glycol (PEG) is modified on the surface of cerium oxide (CeO2) nanoparticles to form a stable polymer coating layer. The polyethylene glycol modification improves the biocompatibility of CeO2 and the uniform dispersion in the hydrogel, reducing its potential toxicity to cells; secondly, Fe-CDs single-atom nanozymes are introduced to simulate the activity of natural peroxidase (POD), catalyze hydrogen peroxide (H2O2) to generate reactive oxygen, and achieve efficient sterilization; under near-infrared light (NIR) irradiation, CeO2 exhibits a certain degree of photothermal conversion performance, and the local high temperature generated can directly kill bacteria, synergistically enhancing the antibacterial effect. In addition, CeO2 has Ce 3+ / Ce 4+ The redox cycle ability can effectively remove excessive reactive oxygen species (ROS), protect healthy tissues, and avoid oxidative damage to healthy tissues caused by reactive oxygen species; CeO2 can remove excess reactive oxygen species and synergize with Fe-CDs nanozymes, which not only improves the antibacterial effect, but also reduces the damage of reactive oxygen species to healthy tissues. Then, carboxymethyl chitosan (CMC) was used as the matrix. The carboxylation modification improved the water solubility and biocompatibility of chitosan and reduced the immune rejection reaction. The carboxyl group (–COOH) in carboxymethyl chitosan can form multiple interactions with the flexible bridge (hydrogen bond) of the PEG chain, effectively preventing the aggregation of CeO2 particles and making them evenly distributed in the hydrogel network. The low-degree carboxymethylated chitosan retains some amino groups and can effectively form Schiff base bonds (C=N double bonds) with glutaraldehyde to achieve cross-linking; Schiff base bonds are easily dissociated in an acidic environment, making the hydrogel have acid-sensitive degradation properties and controlling the release of active ingredients. In the early weakly alkaline environment, the hydrogel exposes Fe-CDs and CeO2 through its microporous structure to achieve high antibacterial efficiency; as the wound gradually becomes acidic, the Schiff base bonds dissociate, triggering the degradation of the hydrogel and releasing the sustained-release repair factors (such as glutathione and sodium hyaluronate) in the PLGA microcapsules to support cell proliferation and tissue regeneration; on this basis, lysine is introduced, and the amino group of lysine can form ionic bonds with the carboxyl group of carboxymethyl chitosan, enhancing the mechanical properties and stability of the hydrogel, and providing additional dynamic cross-linking sites, promoting the regulatory ability of the hydrogel network structure, and providing structural support for the distribution and activity of Fe-CDs nanozymes.
[0012] In addition, polylactic acid-co-glycolic acid (PLGA) microcapsules were introduced into the inner layer. The PLGA microcapsules prepared by double emulsification-solvent evaporation method can be effectively and evenly dispersed in the carboxymethylated chitosan hydrogel matrix. The PLGA microcapsules release active factors (glutathione, sodium hyaluronate, etc.) through degradation, realizing the sustained release function of repair factors and effectively supporting cell repair and tissue regeneration. The introduction of silk fibroin provides natural adhesion sites for cells, significantly promoting cell proliferation and migration; on the other hand, its biodegradable properties cooperate with the sustained release mechanism of PLGA microcapsules to ensure the continuous release of active factors during the wound repair process and play a long-term support role; in addition, silk fibroin can form a complementary sustained release system with PLGA microcapsules. Silk fibroin provides support for early cell adhesion and proliferation, while PLGA microcapsules gradually release pro-repair factors (glutathione and sodium hyaluronate) in the later stage, jointly promoting wound healing. Sodium hyaluronate provides a moisturizing environment in the hydrogel system, which helps to maintain local hydration, optimize the microenvironment of the extracellular matrix (ECM), and ensure a more efficient repair process. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 It is a graph showing the antibacterial performance test results of the composite nanozymes prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 2 It is a cell proliferation test performance test of the composite nanozymes prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 3 It is a pH 5 degradation performance test diagram of the composite nanozymes prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 4 It is a pH 6.5 degradation performance test diagram of the composite nanozymes prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 5 This is a pH 7.4 degradation performance test diagram of the composite nanozymes prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 6 This is a graph showing the test results of active oxygen regulation of the composite nanozymes prepared in Example 2 of the present invention and Comparative Examples 1 to 2; Figure 7 This is a SEM scanning electron microscope image of the composite nanozyme prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0015] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.
[0016] Example 1: A composite nanozyme with antibacterial and pro-repair properties, comprising a main matrix and a core matrix. The main matrix comprises the following raw materials: carboxymethyl chitosan, Fe-CDs single-atom nanozyme, modified CeO2 nanoparticles, lysine, silk fibroin, and glutaraldehyde; the core matrix comprises the following raw materials: PLGA, dichloromethane, glutathione, vitamin E, sodium hyaluronate, glycine, and Tween-80.
[0017] The specific preparation steps of carboxymethyl chitosan are as follows: A1: Add 6 g of chitosan to 200 mL of isopropanol, stir and mix well to obtain a chitosan suspension with a concentration of 3 wt%; add 10 g of sodium hydroxide to 40 mL of deionized water, stir and mix well, then slowly add to 150 mL of the chitosan suspension, stir at 300 rpm for 30 min to obtain pretreated chitosan; A2: Add 7.5 g of chloroacetic acid to 75 mL of deionized water, stir to dissolve evenly, then slowly add to 150 mL of pretreated chitosan prepared in step A1, heat to 50°C in a water bath, react for 4 h, adjust the pH to neutral, filter, wash with deionized water and ethanol repeatedly for 3 times, and vacuum dry at 50°C to constant weight to obtain carboxymethyl chitosan; The specific preparation steps of Fe-CDs single-atom nanozymes are as follows: B1: Dissolve 10g of glucose in 100mL of deionized water, stir thoroughly until completely dissolved, and obtain a carbon source solution with a concentration of 10wt%; dissolve 20g of ferric chloride in 400mL of deionized water, stir thoroughly until completely dissolved, and obtain an iron source solution with a concentration of 5wt%; slowly add 400mL of the iron source solution to 100mL of the carbon source solution, add 4.5g of polyethylene glycol, stir and dissolve evenly, and obtain a precursor solution; B2: Add the precursor solution prepared in step B1 into a polytetrafluoroethylene reactor, set the hydrothermal reaction temperature to 180°C, react for 12 hours, and after the reaction is completed, naturally cool to room temperature, wash with deionized water and anhydrous ethanol repeatedly for 3 times, and vacuum dry at 60°C to constant weight to obtain Fe-CDs precursor powder; B3: The Fe-CDs precursor powder prepared in step B2 was calcined at high temperature under nitrogen atmosphere protection, and the heating rate was set to 5°C / min, and the temperature was raised to 450°C. After maintaining the temperature for 4 hours, it was naturally cooled to room temperature to obtain Fe-CDs single-atom nanozyme; The specific preparation steps of modified CeO2 nanoparticles are as follows: C1: Dissolve 4 g of cerium chloride in 200 mL of deionized water, stir and dissolve evenly to obtain a cerium chloride precursor solution with a concentration of 2 wt%; gradually add 2 M ammonia water to the cerium chloride precursor solution, adjust the pH to 9, continue stirring at 300 pm for 30 min, centrifuge at 8000 rpm for 10 min, filter, wash with deionized water and ethanol repeatedly for 3 times, vacuum dry at 60 ° C for 6 h, and then calcine at 400 ° C for 2 h in an air atmosphere to obtain CeO2 nanoparticles; C2: Dissolve 10g of polyethylene glycol in 200mL of deionized water, stir and dissolve evenly to obtain a polyethylene glycol solution with a concentration of 5wt%; add 1g of CeO2 nanoparticles prepared in step C1 to 200mL of deionized water, and ultrasonically treat at 60W, 40kHz for 15min to obtain a CeO2 dispersion with a concentration of 0.5wt%; C3: Slowly drop 200 mL of CeO2 dispersion prepared in step C2 into 200 mL of polyethylene glycol solution prepared in step C2, stir at 300 rpm at 50°C for 4 h, centrifuge at 10000 rpm for 10 min, filter, wash with deionized water and anhydrous ethanol 3 times, and vacuum dry at 60°C to constant weight to obtain modified CeO2 nanoparticles; The specific preparation steps of the composite nanozyme are as follows: S1: Dissolve 0.4 g glutathione, 0.5 g sodium hyaluronate and 0.1 g glycine in 100 mL deionized water, stir and dissolve evenly to obtain an inner aqueous phase; dissolve 5 g PLGA in 300 mL dichloromethane, stir and dissolve evenly to obtain an organic phase; S2: Slowly add 100 mL of the inner aqueous phase prepared in step S1 to 300 mL of the organic phase prepared in step S1, perform ultrasonic treatment at 300 W for 20 s in an ice bath, then add 0.6 g of vitamin E, and continue ultrasonic treatment for 5 s to obtain a primary emulsion; add 8 g of Tween-80 to 1600 mL of deionized water, stir and mix well, and obtain an external aqueous phase with a concentration of 0.5 wt%; S3: Slowly add 400 mL of the primary emulsion prepared in step S2 to 1600 mL of the external aqueous phase prepared in step S2, perform ultrasonic treatment at 300 W for 30 seconds in an ice bath, then stir at 300 rpm for 4 hours at room temperature, centrifuge at 8000 rpm for 10 minutes, filter, wash with deionized water, and vacuum dry at 60° C. for 8 hours to obtain PLGA microcapsules; S4: Dissolve 2g of carboxymethyl chitosan in 200mL of deionized water, adjust the pH to 6.5, stir and dissolve evenly, and obtain a carboxymethyl chitosan solution with a concentration of 1wt%; disperse 1g of modified CeO2 nanoparticles in 40mL of deionized water, disperse evenly by ultrasonic treatment, and then slowly add to 200mL of carboxymethyl chitosan solution, stir and mix evenly, and then add 0.2g of Fe-CDs single atom nanozyme, stir and mix evenly, and obtain a mixed solution; S5: 1 g of lysine, 1 g of silk fibroin and 4 g of PLGA microcapsules prepared in step S3 were added to 200 mL of the mixed solution prepared in step S4 in sequence, and after stirring and mixing evenly, ultrasonic treatment was performed at 40 W for 5 min, and 4 mL of deionized water was slowly added to prepare a 2.5 wt% glutaraldehyde solution, and the pH was adjusted to 7.4. The reaction was stirred for 30 min at room temperature, and the mixture was allowed to stand at 4 ° C for 12 h, washed with deionized water, and dried naturally to obtain a composite nanozyme.
[0018] Example 2: A composite nanozyme with antibacterial and pro-repair properties, comprising a main matrix and a core matrix. The main matrix comprises the following raw materials: carboxymethyl chitosan, Fe-CDs single-atom nanozyme, modified CeO2 nanoparticles, lysine, silk fibroin, and glutaraldehyde; the core matrix comprises the following raw materials: PLGA, dichloromethane, glutathione, vitamin E, sodium hyaluronate, glycine, and Tween-80.
[0019] The specific preparation steps of carboxymethyl chitosan are as follows: A1: Add 8 g of chitosan to 200 mL of isopropanol, stir and mix well to obtain a chitosan suspension with a concentration of 4 wt%; add 10 g of sodium hydroxide to 45 mL of deionized water, stir and mix well, then slowly add to 180 mL of the chitosan suspension, stir at 300 rpm for 40 min to obtain pretreated chitosan; A2: Add 15 g of chloroacetic acid to 90 mL of deionized water, stir to dissolve evenly, then slowly add to 180 mL of pretreated chitosan prepared in step A1, heat in a water bath to 55°C, react for 3.5 h, adjust the pH to neutral, filter, wash with deionized water and ethanol repeatedly for 3 times, and dry under vacuum at 50°C to constant weight to obtain carboxymethyl chitosan; The specific preparation steps of Fe-CDs single-atom nanozymes are as follows: B1: Dissolve 11g of glucose in 100mL of deionized water, stir thoroughly until completely dissolved, and obtain a carbon source solution with a concentration of 11wt%; dissolve 27.5g of ferric chloride in 500mL of deionized water, stir thoroughly until completely dissolved, and obtain an iron source solution with a concentration of 5.5wt%; slowly add 450mL of the iron source solution to 100mL of the carbon source solution, add 5.5g of polyethylene glycol, stir and dissolve evenly, and obtain a precursor solution; B2: Add the precursor solution prepared in step B1 into a polytetrafluoroethylene reactor, set the hydrothermal reaction temperature to 190°C, react for 10 hours, and after the reaction is completed, naturally cool to room temperature, wash with deionized water and anhydrous ethanol repeatedly for 3 times, and vacuum dry at 60°C to constant weight to obtain Fe-CDs precursor powder; B3: The Fe-CDs precursor powder prepared in step B2 was calcined at high temperature under nitrogen atmosphere protection, and the heating rate was set to 5°C / min, and the temperature was raised to 550°C. After maintaining the temperature for 3 hours, it was naturally cooled to room temperature to obtain Fe-CDs single-atom nanozyme; The specific preparation steps of modified CeO2 nanoparticles are as follows: C1: Dissolve 5 g of cerium chloride in 200 mL of deionized water, stir and dissolve evenly to obtain a cerium chloride precursor solution with a concentration of 2.5 wt%; gradually add 2 M ammonia water to the cerium chloride precursor solution, adjust the pH to 9.5, continue stirring at 300 pm for 45 min, centrifuge at 8000 rpm for 10 min, filter, wash with deionized water and ethanol three times, vacuum dry at 60 ° C for 10 h, and then calcine at 480 ° C for 2 h in an air atmosphere to obtain CeO2 nanoparticles; C2: Dissolve 16 g of polyethylene glycol in 200 mL of deionized water, stir and dissolve evenly to obtain a polyethylene glycol solution with a concentration of 8 wt%; add 2.4 g of CeO2 nanoparticles prepared in step C1 to 300 mL of deionized water, and ultrasonically treat at 70 W, 40 kHz for 12 min to obtain a CeO2 dispersion with a concentration of 0.8 wt%; C3: Slowly drop 250 mL of CeO2 dispersion prepared in step C2 into 200 mL of polyethylene glycol solution prepared in step C2, stir at 300 rpm at 65°C for 4 h, centrifuge at 10000 rpm for 10 min, filter, wash with deionized water and anhydrous ethanol 3 times, and vacuum dry at 60°C to constant weight to obtain modified CeO2 nanoparticles; The specific preparation steps of the composite nanozyme are as follows: S1: Dissolve 0.5g glutathione, 0.55g sodium hyaluronate and 0.15g glycine in 100mL deionized water, stir and dissolve evenly to obtain an inner aqueous phase; dissolve 5g PLGA in 450mL dichloromethane, stir and dissolve evenly to obtain an organic phase; S2: Slowly add 100 mL of the inner aqueous phase prepared in step S1 to 450 mL of the organic phase prepared in step S1, perform ultrasonic treatment at 300 W for 30 seconds in an ice bath, then add 1 g of vitamin E, and continue ultrasonic treatment for 5 seconds to obtain a primary emulsion; add 12.5 g of Tween-80 to 2500 mL of deionized water, stir and mix well, and obtain an external aqueous phase with a concentration of 0.5 wt%; S3: Slowly add 550 mL of the primary emulsion prepared in step S2 to 2500 mL of the external aqueous phase prepared in step S2, perform ultrasonic treatment at 300 W for 40 s in an ice bath, then stir at 300 rpm for 4 h at room temperature, centrifuge at 8000 rpm for 10 min, filter, wash with deionized water, and vacuum dry at 60° C. for 10 h to obtain PLGA microcapsules; S4: Dissolve 2g of carboxymethyl chitosan in 200mL of deionized water, adjust the pH to 6.5, stir and dissolve evenly, and obtain a carboxymethyl chitosan solution with a concentration of 1wt%; disperse 1.5g of modified CeO2 nanoparticles in 40mL of deionized water, disperse evenly by ultrasonic treatment, and then slowly add to 200mL of carboxymethyl chitosan solution, stir and mix evenly, and then add Fe-CDs single atom nanozyme, stir and mix evenly, and obtain a mixed solution; S5: 1.1 g of lysine, 1.6 g of silk fibroin and 10 g of PLGA microcapsules prepared in step S3 were added to 200 mL of the mixed solution prepared in step S4 in sequence, and after stirring and mixing evenly, ultrasonic treatment was performed at 50 W for 4 min, and 8 mL of deionized water was slowly added to prepare a 2.5 wt% glutaraldehyde solution, and the pH was adjusted to 7.4. The reaction was stirred for 50 min at room temperature, and the mixture was allowed to stand at 4 ° C for 20 h, washed with deionized water, and dried naturally to obtain a composite nanozyme.
[0020] Example 3: A composite nanozyme with antibacterial and pro-repair properties, comprising a main matrix and a core matrix. The main matrix comprises the following raw materials: carboxymethyl chitosan, Fe-CDs single-atom nanozyme, modified CeO2 nanoparticles, lysine, silk fibroin, and glutaraldehyde; the core matrix comprises the following raw materials: PLGA, dichloromethane, glutathione, vitamin E, sodium hyaluronate, glycine, and Tween-80.
[0021] The specific preparation steps of carboxymethyl chitosan are as follows: A1: Add 10 g of chitosan to 200 mL of isopropanol, stir and mix well to obtain a chitosan suspension with a concentration of 5 wt%; add 10 g of sodium hydroxide to 50 mL of deionized water, stir and mix well, then slowly add to 200 mL of the chitosan suspension, stir at 300 rpm for 50 min, and obtain pretreated chitosan; A2: Add 20 g of chloroacetic acid to 100 mL of deionized water, stir to dissolve evenly, then slowly add to 200 mL of pretreated chitosan prepared in step A1, heat to 60°C in a water bath, react for 3 h, adjust the pH to neutral, filter, wash with deionized water and ethanol repeatedly for 3 times, and vacuum dry at 50°C to constant weight to obtain carboxymethyl chitosan; The specific preparation steps of Fe-CDs single-atom nanozymes are as follows: B1: Dissolve 12g of glucose in 100mL of deionized water, stir thoroughly until completely dissolved, and obtain a carbon source solution with a concentration of 12wt%; dissolve 30g of ferric chloride in 500mL of deionized water, stir thoroughly until completely dissolved, and obtain an iron source solution with a concentration of 6wt%; slowly add 100mL of the iron source solution to 500mL of the carbon source solution, add 6.6g of polyethylene glycol, stir and dissolve evenly, and obtain a precursor solution; B2: Add the precursor solution prepared in step B1 into a polytetrafluoroethylene reactor, set the hydrothermal reaction temperature to 200°C, react for 6 hours, and after the reaction is completed, naturally cool to room temperature, wash with deionized water and anhydrous ethanol repeatedly for 3 times, and vacuum dry at 60°C to constant weight to obtain Fe-CDs precursor powder; B3: The Fe-CDs precursor powder prepared in step B2 was calcined at high temperature under nitrogen atmosphere protection, and the heating rate was set to 5°C / min, and the temperature was raised to 600°C. After maintaining the temperature for 2 hours, it was naturally cooled to room temperature to obtain Fe-CDs single-atom nanozyme; The specific preparation steps of modified CeO2 nanoparticles are as follows: C1: Dissolve 6 g of cerium chloride in 200 mL of deionized water, stir and dissolve evenly to obtain a cerium chloride precursor solution with a concentration of 3 wt%; gradually add 2 M ammonia water to the cerium chloride precursor solution, adjust the pH to 10, stir continuously at 300 pm for 50 min, centrifuge at 8000 rpm for 10 min, filter, wash with deionized water and ethanol three times, vacuum dry at 60 ° C for 12 h, and then calcine at 500 ° C for 2 h in an air atmosphere to obtain CeO2 nanoparticles; C2: Dissolve 20g of polyethylene glycol in 200mL of deionized water, stir and dissolve evenly to obtain a polyethylene glycol solution with a concentration of 10wt%; add 3g of CeO2 nanoparticles prepared in step C1 to 300mL of deionized water, and ultrasonically treat at 80W, 40kHz for 15min to obtain a CeO2 dispersion with a concentration of 1wt%; C3: Slowly drop 300 mL of CeO2 dispersion prepared in step C2 into 200 mL of polyethylene glycol solution prepared in step C2, stir at 300 rpm at 70°C for 4 h, centrifuge at 10000 rpm for 10 min, filter, wash with deionized water and anhydrous ethanol 3 times, and vacuum dry at 60°C to constant weight to obtain modified CeO2 nanoparticles; The specific preparation steps of the composite nanozyme are as follows: S1: Dissolve 0.6 g glutathione, 0.6 g sodium hyaluronate and 0.2 g glycine in 100 mL deionized water, stir and dissolve evenly to obtain an inner aqueous phase; dissolve 5 g PLGA in 500 mL dichloromethane, stir and dissolve evenly to obtain an organic phase; S2: Slowly add 100 mL of the inner aqueous phase prepared in step S1 to 500 mL of the organic phase prepared in step S1, perform ultrasonic treatment at 300 W for 40 seconds under an ice bath, then add 1.2 g of vitamin E, and continue ultrasonic treatment for 5 seconds to obtain a primary emulsion; add 15 g of Tween-80 to 3000 mL of deionized water, stir and mix well, and obtain an external aqueous phase with a concentration of 0.5 wt%; S3: Slowly add 600 mL of the primary emulsion prepared in step S2 to 3000 mL of the external aqueous phase prepared in step S2, perform ultrasonic treatment at 300 W for 60 s in an ice bath, then stir at 300 rpm for 4 h at room temperature, centrifuge at 8000 rpm for 10 min, filter, wash with deionized water, and vacuum dry at 60° C. for 12 h to obtain PLGA microcapsules; S4: Dissolve 2g of carboxymethyl chitosan in 200mL of deionized water, adjust the pH to 6.5, stir and dissolve evenly to obtain a carboxymethyl chitosan solution with a concentration of 1wt%; disperse 2g of modified CeO2 nanoparticles in 40mL of deionized water, disperse evenly by ultrasonic treatment, then slowly add to 200mL of carboxymethyl chitosan solution, stir and mix evenly, then add 1g of Fe-CDs single atom nanozyme, stir and mix evenly to obtain a mixed solution; S5: 1.2 g of lysine, 2 g of silk fibroin and 10 g of PLGA microcapsules prepared in step S3 were added to 200 mL of the mixed solution prepared in step S4 in sequence, and after stirring and mixing evenly, ultrasonic treatment was performed at 60 W for 5 min, and 10 mL of deionized water was slowly added to prepare a 2.5 wt% glutaraldehyde solution, and the pH was adjusted to 7.4. The reaction was stirred for 60 min at room temperature, and then allowed to stand at 4 ° C for 24 h, washed with deionized water, and dried naturally to obtain a composite nanozyme.
[0022] Comparative Example 1: The operation of Comparative Example 1 is basically the same as that of Example 2, except that in Comparative Example 1, CeO2 nanoparticles are directly used to replace the modified CeO2 nanoparticles.
[0023] Comparative Example 2: The operation of Comparative Example 2 is basically the same as that of Example 2, except that modified CeO2 nanoparticles are not used in Comparative Example 2.
[0024] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 2, except that there is no PLGA microcapsule and its active ingredients (glutathione, sodium hyaluronate, glycine and vitamin E) in Comparative Example 3.
[0025] Comparative Example 4: The operation of Comparative Example 4 is basically the same as that of Example 2, except that no silk fibroin is added in Comparative Example 4.
[0026] Performance Testing: Antibacterial test: fresh bacterial suspensions of Staphylococcus aureus, Escherichia coli and Candida albicans were prepared at a concentration of 1×10 8 CFU / mL, the composite nanozyme samples (50 mg + 10 mL pH 7.4 PBS buffer) prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 were added respectively, the mixed bacterial solution was placed in a constant temperature oscillator at 37°C for 48 h, the total number of colonies in the bacterial solution was recorded by the plate colony counting method, the test was repeated 3 times, the average value was taken, the bacterial solution without the sample was used as the control (the strains used in this experiment were all purchased from the market), and the antibacterial rate was calculated [inhibition rate (%) = (1-the number of bacteria in the control sample / the number of bacteria in the experimental sample) × 100%], the results are as follows Figure 1 shown.
[0027] Depend on Figure 1 The results show that the nanozyme prepared by the present invention still has excellent antibacterial properties under weak alkalinity, and can effectively exert antibacterial effects in the early stages of wounds; from the results of Comparative Example 1 and Example 2, it can be seen that unmodified CeO2 particles may cause them to aggregate more easily in the hydrogel, reducing their dispersibility and antibacterial efficiency in the hydrogel; from the results of Comparative Example 2 and Example 2, it can be seen that the antibacterial efficiency of the composite nanozyme is significantly reduced due to the lack of the synergistic antibacterial effect of CeO2 particles.
[0028] Cell proliferation test: The composite nanozyme samples prepared in Example 2 and Comparative Examples 1 to 4 were placed at the bottom of the culture plate, and 8 wells per group of samples were evenly distributed in a 96-well plate. 50 μL of DMEM medium was added to each well, and then mouse fibroblasts (L929 cells) were diluted to 1×10 4 After culturing for 24 h and 72 h, 5 μL of 5 mg / mL MTT solution was added. After culturing for 4 h, the culture medium in the wells was aspirated, and then 50 μL of dimethyl sulfoxide was added to the wells. The absorbance (OD value) was measured at 490 nm using a microplate reader to measure the activity percentage [cell survival rate (%) = (sample OD value - negative control group OD value) / (positive control group OD value - negative control group OD value) × 100%]. The blank control group contained only culture medium and MTT solution; the negative control group contained untreated cells as a control; the results are shown in Table 1. Figure 2 shown.
[0029] Depend on Figure 2 The results show that the composite nanozyme prepared by the present invention has excellent cell proliferation performance, does not have obvious toxicological damage to cells, and has a significant promoting effect on cell activity after the active ingredients in the PLGA microcapsule are released in the later stage; from the results of comparative example 1 and example 2, it can be seen that unmodified CeO2 may have poor biocompatibility, resulting in increased toxicity and oxidative stress on cells. Unmodified CeO2 may also lead to excessive ROS generation, which is harmful to healthy tissues and inhibits cell proliferation; from the results of comparative example 2 and example 2, it can be seen that the lack of the regulatory effect of CeO2 may cause excessive ROS to cause oxidative damage to cells, and long-term exposure to excessive ROS may cause increased cell damage and decreased proliferation ability; from the results of comparative example 3 and example 2, it can be seen that the lack of PLGA microcapsules and their active ingredients reduces the support for cells, the active ingredients are not released enough, and the cell survival rate is significantly reduced; from the results of comparative example 3 and example 2, it can be seen that the lack of adhesion sites provided by silk fibroin affects the ability of cells to proliferate and migrate, and the proliferation rate is slowed down.
[0030] pH response degradation test: 200 mg of the composite nanozyme sample prepared in Example 2 of the present invention and Comparative Examples 1 to 4 was placed in 100 mL of PBS buffer, and the gradient pH of the PBS buffer was set to 5, 6.5, and 7.4, and immersed in a constant temperature oscillating water bath at 37°C, and the oscillation rate was set to 60 rpm. The samples were taken out at 1 h, 4 h, 8 h, 24 h, 48 h, and 72 h, and the surface moisture was gently absorbed with filter paper. The weight was weighed and recorded, and the degradation rate was calculated as (weight before test - weight at weighing) / weight before test × 100%. The results are as follows: Figure 3 , Figure 4 ,and Figure 5 shown.
[0031] Depend on Figure 3 , Figure 4 and Figure 5 It can be seen from the results that the composite nanozyme sample prepared by the present invention can be effectively and slowly degraded under weakly acidic conditions, and can also be effectively partially degraded under weakly alkaline conditions; from the results of comparative example 1 and example 2, it can be seen that the modified CeO2 is easy to agglomerate in the hydrogel, resulting in uneven dispersion and the formation of structural defects, which may accelerate the degradation rate, resulting in a higher degradation rate in the early stage; from the results of comparative example 2 and example 2, it can be seen that the lack of CeO2 nanoparticles to enhance the mechanical strength of the hydrogel may lead to a weakened structure. In addition, the lack of multiple interactions between CeO2 and CMC may reduce the degree of cross-linking, resulting in excessively fast degradation; from the results of comparative example 3 and example 2, it can be seen that due to the absence of PLGA microcapsules, the hydrogel may be denser, hindering water penetration, resulting in a slower degradation rate; from the results of comparative example 4 and example 2, it can be seen that the degradation of silk fibroin contributes to the degradation of the overall material, and its absence leads to a certain degree of reduction in the degradation rate.
[0032] Active oxygen regulation test: 100 mg of the composite nanozyme sample prepared in Example 2 of the present invention and Comparative Examples 1 to 2 was placed in a PBS buffer solution at pH 7.4 and allowed to stand for 30 minutes, then washed and pretreated, and then the pretreated composite nanozyme sample was placed in 10 mL of 100 μM H2O2 PBS buffer solution, reacted for 30 minutes, and 10 μM DCFH-DA working solution was added. Incubated in dark for 30 minutes, the control group did not add the composite nanozyme sample, only PBS buffer and DCFH-DA working solution were added, and the test was performed at pH 6.5. After culturing for 24 hours and 72 hours, the fluorescence intensity was measured using a fluorescence microplate reader, and the initial fluorescence intensity and the fluorescence intensity after incubation were recorded. The excitation wavelength was 488 nm; the emission wavelength was 525 nm, and the ROS clearance rate was calculated = [1-(fluorescence intensity of the experimental group after treatment-fluorescence intensity of the experimental group before treatment) / (fluorescence intensity of the control group after treatment-fluorescence intensity of the control group before treatment)] × 100%. The results are as follows Figure 6 shown.
[0033] Depend on Figure 6 The results show that the composite nanozyme prepared by the present invention has excellent active oxygen regulation performance. It can preserve more active oxygen in the early stage to achieve antibacterial effect, and can effectively regulate and remove excessive active oxygen in the later stage to avoid affecting healthy cells; from the results of comparative example 1 and embodiment 2, it can be seen that the unmodified CeO2 nanoparticles are easy to agglomerate and have poor dispersibility, which may lead to a decrease in its efficiency in removing ROS; from the results of comparative example 2 and embodiment 2, it can be seen that due to the lack of CeO2 nanoparticles, excessive ROS cannot be effectively removed in the early and late stages.
[0034] Spectrum test: Scanning electron microscope was used to observe the microstructure of the composite nanozyme prepared in Example 2 of the present invention, and a SEM scanning electron microscope image was obtained. The results are as follows: Figure 7 shown.
[0035] Depend on Figure 7 The results show that the composite nanozyme prepared by the present invention has an obvious uniform microporous network with moderate pore size, which is very beneficial to the distribution of functional particles and cell penetration. In addition, the pore wall is relatively smooth and has a cross-linked fiber-like structure of silk fibroin and carboxymethyl chitosan, which is conducive to the binding and distribution of particles (Fe-CDs, CeO2).
[0036] Animal model test: 28 male rats (6-8 weeks old, weighing 200-250 g) were selected to establish a rat wound infection model. A wound with a diameter of 10 mm was cut on the back of each rat, and 50 μL of Escherichia coli suspension (10 8 CFU / mL) was dripped on the wound. After infection, the rats were divided into 7 groups and the composite nanozymes (100 mg) prepared in Example 2 and Comparative Examples 1 to 4 were applied respectively; a negative control group was set up without any treatment, and only physiological saline was applied; a positive control group was coated with 10% povidone iodine solution; a breathable dressing 3M transparent patch was used to cover the wound to fix the hydrogel to prevent it from falling off and being licked by the animal. The dressing was changed every 72 hours. The experiment lasted for 12 days, and the wound healing status was recorded. The wound size of each group of rats was measured in parallel with a digital caliper, and the wound area change healing rate = [(initial wound area-wound area on the day) / initial wound area] × 100% was calculated. The results are shown in Table 1 below.
[0037] Table 1. Wound healing in animal models
[0038] It can be seen from the results in Table 1 that the composite nanozyme prepared by the present invention has excellent antibacterial and repair-promoting effects, and the wound healing rate reaches more than 80% on the 6th day after use, which is an excellent effect; it can be seen from the results of comparative example 1 and example 2 that the dispersibility of unmodified CeO2 is poor, it is easy to agglomerate, and it may have certain toxicity to healthy cells, which leads to a significant impact on the antibacterial effect and wound repair performance; from the lack of comparative example 2 and example 2, the antibacterial and ROS scavenging functions of CeO2 are lacking, only Fe-CDs nanozymes are present, and excessive ROS activity may cause the early healing rate to be affected; from the results of comparative example 3 and example 2, it can be seen that the repair-promoting effect of the active ingredient is indeed poor, and the cell proliferation and reproduction performance in the middle and late stages are extremely poor, resulting in extremely poor wound healing effect; from the results of comparative example 4 and example 2, it can be seen that the lack of silk fibroin leads to the loss of the synergistic effect of promoting cell adhesion and proliferation, and the early cell migration and proliferation are affected, resulting in a relatively slow healing rate.
[0039] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A composite nanozyme for antibacterial and repair-promoting properties, characterized in that: Its composition includes a main matrix and a core matrix, and the composition of the main matrix includes the following raw materials: Carboxymethyl chitosan, Fe-CDs single-atom nanozyme, modified CeO2 nanoparticles, lysine, silk fibroin, glutaraldehyde; the core matrix comprises the following raw materials: PLGA, dichloromethane, glutathione, vitamin E, sodium hyaluronate, glycine, Tween-80; The specific preparation steps of the modified CeO2 nanoparticles are as follows: C1: dissolving cerium chloride in deionized water, stirring and dissolving evenly to obtain a cerium chloride precursor solution; gradually adding 2 M ammonia water to the cerium chloride precursor solution, adjusting the pH, continuously stirring, centrifuging, filtering, repeatedly washing with deionized water and ethanol, vacuum drying, and then calcining in an air atmosphere to obtain CeO2 nanoparticles; C2: dissolving polyethylene glycol in deionized water, stirring and dissolving uniformly to obtain a polyethylene glycol solution; adding the CeO2 nanoparticles prepared in step C1 to deionized water, ultrasonically treating, to obtain a CeO2 dispersion; C3: slowly drop the CeO2 dispersion prepared in step C2 into the polyethylene glycol solution prepared in step C2, continuously stir the reaction, centrifuge, filter, repeatedly wash with deionized water and anhydrous ethanol, and vacuum dry to constant weight to obtain modified CeO2 nanoparticles; In step C3, the volume ratio of the CeO2 dispersion to the polyethylene glycol solution is 1 to 1.5:
1.
2. The antibacterial and repair-promoting composite nanozyme according to claim 1, characterized in that: The specific preparation steps of the carboxymethyl chitosan are as follows: A1: Add chitosan to isopropanol, stir and mix evenly to obtain a chitosan suspension; add sodium hydroxide to deionized water, stir and mix evenly, then slowly add it to the chitosan suspension, stir and obtain pretreated chitosan; A2: Add chloroacetic acid to deionized water, stir to dissolve evenly, then slowly add to the pretreated chitosan prepared in step A1, heat in a water bath, react, adjust the pH to neutral, filter, repeatedly wash with deionized water and ethanol, and vacuum dry at 50°C to constant weight to obtain carboxymethyl chitosan.
3. The antibacterial and repair-promoting composite nanozyme according to claim 2, characterized in that: In step A1, the ratio of the amount of sodium hydroxide, deionized water and chitosan suspension is 1 g: 4-5 mL: 15-20 mL.
4. The antibacterial and repair-promoting composite nanozyme according to claim 3, characterized in that: In step A2, the ratio of the amount of chloroacetic acid, deionized water and pretreated chitosan is 0.05-0.1 g: 0.5 mL: 1 mL.
5. The antibacterial and repair-promoting composite nanozyme according to claim 4, characterized in that: The specific preparation steps of the Fe-CDs single-atom nanozyme are as follows: B1: Dissolve glucose in deionized water and stir thoroughly until completely dissolved to obtain a carbon source solution; dissolve ferric chloride in deionized water and stir thoroughly until completely dissolved to obtain an iron source solution; Slowly add the iron source solution to the carbon source solution, add polyethylene glycol, stir and dissolve evenly to obtain a precursor solution; B2: Add the precursor solution prepared in step B1 into a polytetrafluoroethylene reactor, set the hydrothermal reaction temperature, and after the reaction is completed, naturally cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol, and vacuum dry to constant weight to obtain Fe-CDs precursor powder; B3: The Fe-CDs precursor powder prepared in step B2 is calcined at high temperature under nitrogen atmosphere protection, the heating rate is set to 5°C / min, the temperature is increased, and the temperature is maintained for 2 to 4 hours, and then naturally cooled to room temperature to obtain Fe-CDs single-atom nanozyme.
6. The antibacterial and repair-promoting composite nanozyme according to claim 1, characterized in that: In step B1, the volume ratio of the iron source solution to the carbon source solution is 4-5:1; the added amount of polyethylene glycol is 10% of the total mass of glucose and ferric chloride.
7. A method for preparing the antibacterial and repair-promoting composite nanozyme according to any one of claims 1 to 6, characterized in that: The specific preparation steps are as follows: S1: dissolving glutathione, sodium hyaluronate and glycine in deionized water, stirring and dissolving them uniformly to obtain an inner aqueous phase; dissolving PLGA in dichloromethane, stirring and dissolving them uniformly to obtain an organic phase; S2: slowly adding the inner aqueous phase prepared in step S1 to the organic phase prepared in step S1, ultrasonically treating in an ice bath, then adding vitamin E, and continuing the ultrasonic treatment to obtain a primary emulsion; adding Tween-80 to deionized water, stirring and mixing to obtain an outer aqueous phase; S3: slowly adding the primary emulsion prepared in step S2 to the external aqueous phase prepared in step S2, ultrasonically treating in an ice bath, and then stirring at room temperature, centrifuging, filtering, washing with deionized water, and vacuum drying to obtain PLGA microcapsules; S4: dissolving carboxymethyl chitosan in deionized water, adjusting the pH, stirring and dissolving uniformly to obtain a carboxymethyl chitosan solution; dispersing the modified CeO2 nanoparticles in deionized water, dispersing uniformly by ultrasonic treatment, and then slowly adding the modified CeO2 nanoparticles to the carboxymethyl chitosan solution, stirring and mixing uniformly, and then adding the Fe-CDs single-atom nanozyme, stirring and mixing uniformly to obtain a mixed solution; S5: Add lysine, silk fibroin and PLGA microcapsules prepared in step S3 to the mixed solution prepared in step S4 in sequence, stir and mix evenly, perform ultrasonic treatment, slowly drop glutaraldehyde solution prepared with deionized water, adjust the pH, stir the reaction at room temperature, let stand, wash with deionized water, and dry naturally to obtain a composite nanozyme.
8. The method for preparing an antibacterial and repair-promoting composite nanozyme according to claim 7, characterized in that: In step S1, the ratio of the amount of glutathione, sodium hyaluronate, glycine and deionized water is 0.4-0.6g:0.5-0.6g:0.1-0.2g:100mL; the ratio of the amount of PLGA to dichloromethane is 1g:60-100mL; in step S2, the volume ratio of the inner aqueous phase to the organic phase is 1:3-5; the added concentration of vitamin E is 1.5-2mg / mL.
9. The method for preparing an antibacterial and repair-promoting composite nanozyme according to claim 8, characterized in that: In step S3, the volume ratio of the primary emulsion and the external aqueous phase is 1:4-5; in step S4, the ratio of the modified CeO2 nanoparticles, deionized water and carboxymethyl chitosan solution is 0.5-1 g:20 mL:100 mL; the ratio of the Fe-CDs single-atom nanozyme and carboxymethyl chitosan solution is 0.1-0.5 g:100 mL.
10. The method for preparing an antibacterial and repair-promoting composite nanozyme according to claim 9, characterized in that: In step S5, the ratio of the amount of lysine, silk fibroin, PLGA microcapsules and the mixed solution is 0.5-0.6 g: 0.5-1 g: 2-5 g: 100 mL; the amount of the glutaraldehyde solution added is 2-5% of the volume of the mixed solution.
Citation Information
Patent Citations
Preparation method and use of nano-cerium dioxide material
CN109607591A
Cerium dioxide nano particle as well as preparation method and application thereof
CN116553596A
Fe-CDs nano-enzyme antibacterial hydrogel as well as preparation method and application thereof
CN118217444A
Composite nano-enzyme for promoting wound healing and preparation method thereof
CN118717978A
Programmed hydrogel loaded with double nano-enzymes as well as preparation method and application of programmed hydrogel
CN118845626A
Cited By
Process method for eluting and removing granular nutritive salt in water body
CN119660929A